Viral Causes of Lymphoma: The History of Epstein-Barr Virus and Human T-Lymphotropic Virus 1. Issue 1 (25th September 2017) - Esau, Daniel
In 1964, Epstein, Barr, and Achong published a report outlining their discovery of viral particles in lymphoblasts isolated from a patient with Burkitt lymphoma. The Epstein-Barr virus (EBV) was the first human cancer virus to be described, and its discovery paved the way for further investigations into the oncogenic potential of viruses. In the decades following the discovery of EBV, multinational research efforts led to the discovery of further viral causes of various human cancers. Lymphomas are perhaps the cancer type that is most closely associated with oncogenic viruses: infection with EBV, human T-lymphotropic virus 1 (HTLV-1), human immunodeficiency virus (HIV), Kaposi sarcoma-associated herpesvirus/human herpesvirus 8, and hepatitis C virus have all been associated with lymphomagenesis. Lymphomas have also played an important role in the history of oncoviruses, as both the first human oncovirus (EBV) and the first human retrovirus (HTLV-1) were discovered through isolates taken from patients with unique lymphoma syndromes. The history of the discovery of these 2 key oncoviruses is presented here, and their impact on further medical research, using the specific example of HIV research, is briefly discussed.